Supraventricular tachycardias: differential diagnosis at bedside and in the electrophysiology laboratory. Issue 3 (September 2016) - Katritsis, D. G.
Abstract: Clinical and electrophysiologic criteria used for the differential diagnosis of regular supraventricular tachycardias (SVT) are presented. Although several electrocardiographic clues may assist differential diagnosis, this is usually accomplished at electrophysiology study and, most often, is between atrioventricular nodal reentrant tachycardia, atrioventricular reentrant tachycardia due to a concealed accessory pathway, and atrial tachycardia. Atrial and, mainly, ventricular pacing maneuvers during sinus rhythm or tachycardia have been used with variable success rate. In clinical practice, these techniques cannot be applied to all cases, and multiple criteria have to be used for the differential diagnosis of narrow complex tachycardias with atypical characteristics. Answer questions and earn CME: https://wileyhealthlearning.com/Activity2/4469457/Activity.aspx